Price and volume effects of changes in MSCI indices – nature and causes - Chakrabarti, Rajesh; Huang, Wei; Jayaraman, Narayanan; Lee, Jinsoo (Journal of Banking & Finance, 2005)
Using changes in the MSCI Standard Country Indices for 29 countries between 1998 and 2001, we document that stock returns and volumes exhibit “index effects” in international markets similar to those detected by the studies of US stocks. The stocks added to the indices experience a sharp rise in prices after the announcement and a further rise during the period preceding the actual change, though part of the gain is lost after the actual change date. The stocks that are deleted from the indices, on the other hand, witness a steady and marked decline in their prices. Trading volumes increase significantly and remain at high levels after the change date for the added stocks. There are also considerable cross-country variations in these effects. Tests using data on various measures reflecting the different hypotheses fail to turn up any evidence in support of information effects. Our evidence appears to be more supportive of the downward sloping demand curve hypothesis. There is some evidence of price-pressure and mild evidence of liquidity effect, particularly in Japan and UK.